Pedagogical Implications for Using a Wiki in Peer-to-Peer Learning Environments (LEARNing Landscapes, 2018)
The pedagogical potentials and challenges experienced when trying to incorporate the use of a wiki social media site with undergraduate childhood study students are reported. The wiki was introduced to inspire students to engage in student peer-learning, develop their writing skills, and facilitate a PhD student’s developmental teaching beyond the dissertation phase from PhD student to scholar. Although these aims were achieved to a degree, they were reached in unexpected ways. A “community of practice” (Lave & Wenger, 1991) was evident within the actual seminar session space rather than within an online community capacity.
Keywords: student centered learning; participatory learning; community of practice